ERO1α regulates curcumin-induced autophagy via PI3K/AKT pathway - Dandan Huang; Bolorchimeg Baldandorj; Erdenezaya Odkhuu; Egshiglen Amartuvshin; Damdindorj Boldbaatar; Hairong Guo; Adilsaikhan Mendjargal (Cancer Treatment and Research Communications, 2025)
Objective: Through comprehensive analysis of cisplatin-resistant HeLa cervical cancer cells, we reveal that curcumin exerts potent anti-cancer effects by modulating autophagic processes, and further identify Endoplasmic reticulum oxidoreductase 1-alpha (ERO1α) as a key regulator mediating this biological response. Methods: Cell proliferation was assessed using Cell Counting Kit-8 (CCK-8). The immunoblotting analysis measured the Phosphoinositide 3-Kinase/ Protein Kinase B (PI3K/AKT) pathway-related proteins, Microtubule-associated protein 1A/1B-light chain 3 (LC3II/I) ratio, and Beclin-1 expression. The cell migration ability was evaluated through a scratch assay. Results: Curcumin significantly inhibits the proliferation and migration of cisplatin-resistant HeLa cells. It promotes autophagy in these cells, as shown by the upregulation of autophagy-related proteins Beclin-1 and LC3II/I. Curcumin also downregulates ERO1α expression, subsequently modulating the PI3K/AKT pathway. Interestingly, the overexpression of ERO1α or activation of PI3K negated the autophagy-promoting effects of curcumin, indicated by the absence of changes in autophagy-related proteins and phosphorylation levels of PI3K/AKT. Conclusions: Our study provides compelling evidence that curcumin inhibits the proliferation and migration of cisplatin-resistant HeLa cells by promoting autophagy through the downregulation of ERO1α and inhibition of the PI3K/AKT pathway.